The Chemistry and Biological Activities of Anthraquinones from the Cell Suspension Culture of Morinda Elliptica and Flavonoids from Hedychium Thyrsiforme - Karim, Jasril (2002)
Peninsular Malaysia is one of the mega diverse countries of the world. The Malaysian people have used these plants for medicinal purpose long before the development of modern medicine to treat various diseases. As part of intensive studies on medicinal plants particularly in Universiti Putra Malaysia (UPM), this research has been conducted to study the chemistry and biological activities of several selected plants as well as compounds isolated from the cell suspension culture of Morinda elliptica and the rhizome parts of Hedychium thyrsiforme. Based on literature search there have not been any reports on this particular research subjects. Eight antbraquinones including nordamnacanthal (A-I), alizarin-I-methyl ether (A-2), antbragallol- l,2-dimethyI ether (A-3), purpurin-I-methyl ether (A-4), rubiadin (A-5), soranjidiol (A-6), lucidin-<o-methyl ether (A-7) and morindone (A-8) were isolated from the cell suspension culture of Morinda elliptica. Five f1avonoids including 3,7.4' -trimethoxy-5-hydroxyflavone (F - 1), 3,4' -dimethoxy-5, 7 -dihydroxyflavone (F-2), 5,7.4' -trimethoxy-3-hydroxyflavone (F-3), 3,5,7,4' -tetramethoxyflavone (F-4) and 7,4'-dimethoxy-3,5-dihydroxyflavone (F-5) were also isolated from the rhizome parts of Hedychium thyrsiforme. The structures of all the isolated compounds were established based on spectral data including ultraviolet-visible, infrared, mass and nuclear magnetic resonance spectra. The study on biological activities of the isolated compounds was conducted using some in vitro bioassay procedures. In antitumor promoting assay, it is interesting to note that nordamnacanthal and 5,7,4'-trimethoxy-3-hydroxyflavone in concentration of 0.4 J.lglml showed strong inhibition activity towards Epstein-Barr virus activation in Raji cells. Nordamnacanthal and 5,7,4'-trimethoxy-3- hydroxyflavone as well as morindon, 3,4'-dimethoxy-5,7-dihydroxy-flavone and 7,4'-dimethoxy-3,5-dihydroxyflavone also showed strong antioxidant activity.